The Characteristics and Distribution of Nerve Plexuses in the Dartos Fascia From Concealed Penis Children - Huang, WenFang; Tang, DaXing; Gu, WeiZhong (Frontiers in Pediatrics, 2021)
The purpose of this study is to analyze the nerve plexus distribution in dartos fascia of concealed penis(CP). A total of 28 CP patients met ASA category I and II were included, with median age of 3.5 years (8 months to 5 years). During the surgery, tissue samples of dartos fascia at points 3, 6, 9, and 12 o’clock of the penile shaft were collected. Standard hematoxylin and eosin (H&E) staining and S-100 immunohistochemical staining were used to analyze the nerve plexus distribution among different positions. The number of nerve plexuses in superficial fascia collected at the 6 o’clock position of the penile shaft was the most abundant among four positions (median 7.25, ranged 1 to 24). The abundant nerve plexuses in the dartos fascia of CP patients, especially at the 6 o'clock position, indicate that the surgery on the preputial frenulum should avoid damage to the dartos fascia,as it might be related to maintain the erection and sexual function in adolescence.